The Acute Response of Apoptosis and Migration to Resistance Exercise Is Protocol-Dependent - Prestes, J.; Pereira, G. B.; Tibana, R. A.; Navalta, J. W. (International Journal of Sports Medicine, 2014)
The aim of the present study was to compare the acute effects of resistance exercise (RE) designed for hypertrophy or local muscle endurance (LME) on CD4+ and CD8+ T cell apoptosis and migration. 14 untrained subjects (age 20.5±0.8 years, body mass 70.0±12.8 kg, body mass index 24.0±3.2 kg/m2), women (N=11) and men (N=3) completed 2 RE sessions (3 sets of 9 exercises) designed for hypertrophy at 10 repetitions maximum (RM) and LME at 60% of 10RM with 1-min rest-intervals between sets and exercises. The investigated lymphocytes were: CD4+, CD4+/CD69RA+, CD8+ and CD8+/CD69RA+ with cell surface markers annexin V and CX3CR1 analyzed by flow cytometry. Percentage of CD4+ positive for annexin V+ were higher immediately following and 24 h after the hypertrophy protocol as compared with LME, while CD4+ positive for CX3CR1 were higher immediately after and lower at the 24 h time point after LME as compared with the hypertrophy session. CD8+ lymphocytes responded similarly to the hypertrophy and LME protocols with elevations in both cellular migration and cell death immediately following and 24 h after the bouts (p≤0.05). Considering that the acute response of CD4+ lymphocytes to RE is protocol-dependent, a gradual adaptation to a hypertrophy program could minimize the effect on CD4+ lymphocytes and reduce the potential susceptibility to antigens during this timeframe. This would also be interesting for a RE program designed for LME based on the observed CD8+ lymphocyte response.
Keywords: resistance training; immune response; T lymphocyte; cell migration; programmed cell death